Aggrecan expression, a component of the inhibitory interneuron perineuronal net, is altered following an early life seizure - McRae, Paulette A. (2010)
The perineuronal net (PN), a component of the neural extracellular matrix (ECM), is a dynamic structure whose expression decreases following diminished physiological activity. Here, we analyzed the effects of increased neuronal activity on the development of aggrecan, a component of the PN, in the hippocampus. We show aggrecan expression to be prominent around parvalbumin (PV) interneurons in the postnatal hippocampus. Moreover, after seizure induction in early life there was a significant increase in aggrecan expression in a region specific manner during the course of development. We conclude that increased neuronal activity leads to accelerated expression of PNs in the hippocampus that attenuates in the adult hippocampus. This study shows the dynamic nature of the PN component of the ECM and the role neuronal activity has in molding the extracellular milieu of inhibitory interneurons.